Postrzegane relacje rodzice-dzieci a realizacja zadań rozwojowych okresu dorastania = Observed parenting practices vs. the realization of developmental tasks in adolescence - Grzegorzewska, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The problem focused on is the relationship of maternal and paternal parenting behavior in adolescence to developmental tasks in families with alcohol problems and in non-problems families. In alcoholic families, drinking leads to multiple family stressors including disrupted parenting characterized by a lack of love and poor discipline. In the present work it is assumed that observed parenting practices would be one of important risk or protective factors in families with adolescents.
Keywords: rodzina; rodzina z problemem alkoholowym; młodzież i młodzi dorośli; relacje rodzic-młodzież; zachowania ryzykowne